Case studies of high-rise buildings - Babak Raji; Martin J. Tenpierik; Andy van den Dobbelsteen (A+BE: Architecture and the Built Environment)
Tall buildings are being designed and built across a wide range of cities. A poorly designed tall building can tremendously increase the building’s appetite for energy. Therefore, this paper aims to determine the design strategies that help a high-rise office building to be more energy efficient. For this purpose, a comparative study on twelve case buildings in three climate groups (temperate, sub-tropical & tropical) was performed. The exterior envelope, building form and orientation, service core placement, plan layout, and special design elements like atria and sky gardens were the subject of investigation. The effectiveness of different design strategies for reducing the cooling, heating, ventilation and electric lighting energy were analysed. Finally, lessons from these buildings were defined for the three climates. Furthermore, a comparison of building energy performance data with international benchmarks confirmed that in temperate and sub-tropical climates sustainable design strategies for high-rise buildings were performing well, as a result leading to lower energy consumption. However, for the tropics the design of high-rise buildings needs higher concern.